Ocorrência, sorotipagem e rsistência antimicrobiana de Streptococcus suis em funcionários e ambente de abatedouro de sínos - Soares, Taíssa Cook Siqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present study aimed to determine the occurrence of Streptococcus suis in employees (healthy carriers) and environment of swine slaughterhouses with federal inspection service of the state of São Paulo, Brazil, to describe the distribution of the different types of the agent and the antimicrobial susceptibility profile of the isolated strains, as well as to research the risk factors associated with the occurrence of the pathogen. Tonsillar swabs of 139 employees and 261 environmental swabs were collected for detection of S. suis and its types by monoplex and multiplex PCR, respectively. There was no detection of healthy carriers employees. S. suis was isolated from 27.03% of the samples collected at slaughterhouse A; 17.31% at slaughterhouse B; 15.31% at slaughterhouse C; and 36.36% at slaughterhouse D. Significant statistical differences (p<0.05) were observed for the occurrence of S. suis among slaughterhouses and among areas of low, medium and high risk of the slaughterhouse A. The types 4 (20.00%), 5 (20.00%), 12 (20.00%) and 29 (20.00%) were the most frequent followed by types 21 (10.00%) and 31 (10.00%). The most effective antimicrobials were amoxicillin-clavulanate (100.00%), doxycycline (100.00%), ceftiofur (93.75%), ampicillin (81.25%) and cephalexin (75.00%). Multidrug resistance was observed in 100.00% of the isolates. The slaughterhouses and the different areas of the pig slaughtering may be risk factors for the occurrence of S. suis and, consequently, for human infection. However, it is noteworthy that all employees are exposed to S. suis infection. This project is the first epidemiological study in Brazil about the risk factors associated with the occurrence of S. suis involving a large numbers of individuals belonging to the main risk group

O presente estudo teve por objetivos determinar a ocorrência de Streptococcus suis em funcionários (portadores sadios) e ambiente de abatedouros com SIF do estado de São Paulo, Brasil, descrever a distribuição dos diferentes tipos do agente e o perfil de suscetibilidade aos antimicrobianos das linhagens isoladas, bem como pesquisar os fatores de risco associados à ocorrência do patógeno. Suabes de tonsilas de 139 funcionários e 261 suabes ambientais foram coletados para detecção de S. suis e seus tipos através das técnicas de monoplex e multiplex PCR, respectivamente. Não houve detecção de funcionários portadores sadios. S. suis foi isolado de 27,03% das amostras coletadas no abatedouro A; 17,31% no abatedouro B; 15,31% no abatedouro C; e 36,36% no abatedouro D. Diferença estatisticamente significativa (p<0,05) foi observada para as ocorrências de S. suis entre os abatedouros e entre as áreas de risco baixo, médio e alto da etapa de matança no abatedouro A. Os tipos 4 (20,00%), 5 (20,00%), 12 (20,00%) e 29 (20,00%) foram os mais frequentes seguidos pelos tipos 21 (10,00%) e 31 (10,00%). Os antimicrobianos mais eficazes foram amoxicilina com clavulanato (100,00%), doxiciclina (100,00%), ceftiofur (93,75%), ampicilina (81,25%) e cefalexina (75,00%). Multirresistência foi observada em 100,00% das linhagens isoladas. Os abatedouros e as diferentes áreas da etapa de matança podem ser fatores de risco para a ocorrência de S. suis, consequentemente, para infecção humana pelo patógeno. No entanto, é importante ressaltar que todos os funcionários estão expostos à infecção. O presente trabalho é o primeiro estudo epidemiológico realizado no Brasil acerca dos fatores de risco associados à ocorrência de S. suis envolvendo grande número de indivíduos pertencentes ao principal grupo de risco
Ocurrence, serotyping and antimicrobial resistence of Streptococcus suis in employees and environment of swine slaughterhouses
Keywords: Estreptococo; Epidemiologia - Pesquisa; Agentes anti-inflamatorios; Trabalhadores - Fatores de risco; Matadouros; Slaughtering and slaughter-houses